IEEE International Symposium on Intelligent Control 2006
DOI: 10.1109/isic.2006.285637
|View full text |Cite
|
Sign up to set email alerts
|

Robust H¿ Fixed Order Control Strategies for Large Scale Web Winding Systems

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A MATLAB software called HIFOO (H-Infinity Fixed-Order Optimization) has been released in late 2005 [15], and uses local optimization techniques. This software, used in this work, has also been used for the reduced order controller calculation in web handling systems with load cells [17].…”
Section: Reduced Order Centralized Control Designmentioning
confidence: 99%
“…A MATLAB software called HIFOO (H-Infinity Fixed-Order Optimization) has been released in late 2005 [15], and uses local optimization techniques. This software, used in this work, has also been used for the reduced order controller calculation in web handling systems with load cells [17].…”
Section: Reduced Order Centralized Control Designmentioning
confidence: 99%
“…7. In previous studies (Knittel, et al, 2006b) each controller dedicated to each subsystem was synthesized separately. Now, the decentralized controllers are calculated in one step (for a plant with reduced number of motors) taken into account the interactions between consecutive subsystems.…”
Section: Decentralized Control With Feedforwardmentioning
confidence: 99%
“…Other H ∞ control strategies with full order are presented in (Knittel, et al, 2006a) and with reduced order and full structure in (Knittel, et al, 2006b). It is shown that such a strategy leads to much improved web tension and velocity regulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…A decentralized adaptive controller with model based feedforward was developed and experimentally verified in [12]. As the web processing plants are known as highly resonant systems with strong coupling between the variables to control, several improvements of multivariable controllers based on robust control have been introduced to address the resonant effects and tension control while maintaining performance [13][14][15][16][17][18][19][20]. Although most of these methods resulted in acceptable control performance, they relied too heavily on the system model.…”
Section: Introductionmentioning
confidence: 99%